Character Strengths in Adults and Adolescents: Their Measurement and Association with Well-Being. Issue 1 (2nd January 2023) - Kretzschmar, André; Harzer, Claudia; Ruch, Willibald
Abstract: Character strengths are assessed in adults and adolescents using different measurements. However, a comparison of character strengths across age groups requires the equivalence of these measurements. The present study examined the comparability of the two questionnaires most frequently used in research: The VIA Inventory of Strengths (VIA-IS) for adults and the VIA Inventory of Strengths for Youth (VIA-Youth). A sample of N  = 170 high-school students in the age of about 18 years and up to two informants ( N  = 164 mostly parents; N  = 156 mostly friends and partners) completed both character strengths questionnaires and several well-being questionnaires. The psychometric characteristics and the correlations with well-being scales were examined once exclusively on the basis of self-rating and once on the basis of combined self- and informant-ratings. Substantial differences between the questionnaires were found in each of the criteria examined (e.g., identification of signature strengths, or largest associations with well-being). The results indicate that VIA-IS and VIA-Youth measure character strengths differently, so that a comparison across age groups may lead to biased conclusions. Therefore, differences in character strengths between adults and adolescents should not be exclusively interpreted in terms of differences on the trait level as these differences may be caused by nonequivalent questionnaires.